The Onset of Soret Driven Ferrothermoconvective Instability in the Presence of Darcy Porous Medium with Anisotropy Effect and MFD Viscosity - D. Murugan; R. Sekar (International Journal of Applied Mechanics and Engineering, 2021)
The effect of magnetic field dependent (MFD) viscosity on Soret driven ferrothermohaline convection in a densely packed anisotropic porous medium has been studied. The Soret effect is focused on the system. A linear stability analysis is carried out using a normal mode technique and a perturbation method is applied. It is found that a stationary mode is favorable for the Darcy model. Vertical anisotropy tends to destabilize the system and the magnetization effect is found to stabilize the system. It is also found that the MFD viscosity delays the onset of convection. Numerical computations are made and illustrated graphically.